SELECTED PUBLICATIONS IN THE COLLECTION OF THE VIRTUAL MUSEUM OF THE ORANGE ALTERNATIVE (FROM FYDRYCH TO MISZTAL) AS AN EXАMPLE OF “SAVED MEMORY” - A CONTRIBUTION TO THE ANALYSIS (Slavic Studies, 2025)
This text is a contribution to the study of programmatic texts and publications related to the Orange Alternative protest-art movement. The author presents the most important publications found in the collection of the virtual Museum of the Orange Alternative, with particular emphasis on Waldemar “Major” Fydrych’s Manifesto of Socialist Surrealism and essayistic-scientific texts.
Keywords: Orange Alternative; manifesto; Museum of the Orange Alternative; publication